2013
DOI: 10.1097/scs.0b013e31827ff2b6
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Calvarial Bone Healing Capacity

Abstract: Tissue engineering of bone with hyaluronan-based hydrogel shows good healing of cranial defects, comparable with bone autografts. The hydrogel itself may represent a novel alternative to autologous bone transplants in craniofacial bone repair. The study also reveals a general superior healing capacity in the frontal bone as compared to parietal/temporal bones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…Recently, a novel polymer hydrogel of sugarcane molasses appeared to be a good candidate to treat calvarial bone defects in rats, in association with Bone Morphogenetic Proteins (BMPs) [43]. In patients, hyaluronan-based hydrogels associated with BMP-2 greatly enhanced the healing of critical-size cranial defects [44] or alveolar cleft defects [45], and alginate-agarose hydrogels combined with autologous chondrocytes significantly improved clinical outcome in patients suffering from chondral or osteochondral defects over a 2-year follow-up [46]. …”
Section: Discussionmentioning
confidence: 99%
“…Recently, a novel polymer hydrogel of sugarcane molasses appeared to be a good candidate to treat calvarial bone defects in rats, in association with Bone Morphogenetic Proteins (BMPs) [43]. In patients, hyaluronan-based hydrogels associated with BMP-2 greatly enhanced the healing of critical-size cranial defects [44] or alveolar cleft defects [45], and alginate-agarose hydrogels combined with autologous chondrocytes significantly improved clinical outcome in patients suffering from chondral or osteochondral defects over a 2-year follow-up [46]. …”
Section: Discussionmentioning
confidence: 99%
“…Hemostatic gelatin sponges have been demonstrated as a suitable in vitro model for producing 3-dimensional (3D) human and bovine chondrocyte cultures 21 22 23 . While some studies have demonstrated the usefulness of hemostatic gelatin sponges as a carrier or an implant for repairing gingival depressions and bone defects 24 25 26 27 , these studies only demonstrated the suitability of gelatin sponge as a carrier or an implant for bone regeneration. For example, Arias-Gallo et al .…”
mentioning
confidence: 99%
“…used gelatin sponges as a carrier of fibroblast growth factors 26 and Skogh et al . applied gelatin sponges as an implant for bone regeneration 27 . These studies did not demonstrate their usefulness in regards to cell differentiation.…”
mentioning
confidence: 99%
“…Indeed, most of these studies underlined the benefits that the HA derivatives, either as hydrogel or solid mesh, exerted in human diseases such as venous ulcers [107],[108], decubitus ulcers [109], oral mucosal lesions [110], surgical ablation of nevi/cutaneous tumors and cicatritial outcomes [111], talar dome and knee osteochondral lesions [112],[113], and cranial bone regeneration [114]. So far, no clinical trial started to verify whether such biomaterial can be useful also to repair the infarcted myocardium.…”
Section: Discussionmentioning
confidence: 99%